Drinking water and rural schools in the Western Amazon: an environmental intervention study - Maura Regina Ribeiro; Luiz Carlos de Abreu; Gabriel Zorello Laporta (PeerJ, 2018)
Background Although water and sanitation are considered human rights, worldwide approximately three of 10 people (2.1 billion) do not have access to safe drinking water. In 2016, 5.6 million students were enrolled in the 34% of Brazilian schools located in rural areas, but only 72% had a public water supply network. The objective was to evaluate effectiveness of environmental intervention for water treatment in rural schools of the Western Amazonia, and determine the efficacy of water treatment using a simplified chlorinator on potability standards for turbidity, fecal coliforms and Escherichia coli. Methods A simplified chlorinator was installed for treatment of potable water in 20 public schools in the rural area of Rio Branco municipality, Acre state, Brazil. Results Before the intervention, 20% (n = 4), 100% (n = 20) and 70% (n = 14) of schools had water that failed to meet potability standards for turbidity, fecal coliforms and E. coli, respectively. However, after intervention, 70% (p = 0.68), 75% (p < 0.001) and 100% (p < 0.001) of schools complied with potability standards. Discussion This intervention considerably improved schools’ water quality, thus decreasing children’s health vulnerability due to inadequate water. Ancillary activities including training, educational lectures, installation of equipment, supply of materials and supplies (65% calcium hypochlorite and reagents) were considered fundamental to achieving success full outcomes. Installation of a simplified chlorinator in rural schools of the Western Amazon is therefore proposed as a social technology aiming at social inclusion, as well as economic and environmental sustainability.